2002
DOI: 10.1002/ana.10263
|View full text |Cite
|
Sign up to set email alerts
|

A nonischemic forearm exercise test for McArdle disease

Abstract: Ischemic forearm exercise invariably causes muscle cramps and pain in patients with glycolytic defects. We investigated an alternative diagnostic exercise test that may be better tolerated. Nine patients with McArdle disease, one with the partial glycolytic defect phosphoglycerate mutase deficiency, and nine matched, healthy subjects performed the classic ischemic forearm protocol and an identical protocol without ischemia. Blood was sampled in the median cubital vein of the exercised arm. Plasma lactate level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 24 publications
2
61
2
2
Order By: Relevance
“…The test requires insertion of a venous catheter for blood sampling and invariably results in muscle cramps that may cause muscle injury in McArdle's disease patients. 9 -11 Although unpleasant side effects can be avoided by performing a modified aerobic exercise test, 11 the test can be technically difficult because it ideally requires monitoring of the force output and immediate analysis of plasma ammonia, due to the labile nature of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…The test requires insertion of a venous catheter for blood sampling and invariably results in muscle cramps that may cause muscle injury in McArdle's disease patients. 9 -11 Although unpleasant side effects can be avoided by performing a modified aerobic exercise test, 11 the test can be technically difficult because it ideally requires monitoring of the force output and immediate analysis of plasma ammonia, due to the labile nature of this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Eccentric exercise has been widely used in human and animal studies of DOMS, many of which have found histological Friden and Lieber 1998;McCurry and Faulkner 1985), ultrastructural (Newham et al 1983;Ogilvie et al 1988), biochemical Blais et al 1999;Ostrowski et al 1998), and physical (see Proske and Morgan 2001 for review) changes. Lactic acid was long considered to be responsible for DOMS, but this belief has been largely rejected because of the failure of higher levels of lactate to induce soreness in concentric exercise (Armstrong 1984;Schwane et al 1983) or in McArdle's disease (Kazemi-Esfarjani et al 2002), a different time course for soreness and the blood lactate increase after exercise , and other findings. Although there has been dispute as to whether an inflammatory process is involved in the underlying mechanisms of DOMS (see Smith 1991 for review), the possibility cannot be excluded that some inflammatory mediators or cytoplasmic components, released from muscle cells as a result of the micro-injury after eccentric contraction, may sensitize the nociceptors to mechanical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five per cent of patients develop fixed skeletal muscle weakness, which predominantly involves upper limbs [6,7]. Both ischaemic [8] and nonischaemic [9] forearm exercise tests can then be performed, where the absence of elevated pyruvate and lactate in venous blood from the contracting forearm is considered indicative of McArdle disease.…”
Section: Methodsmentioning
confidence: 99%